2014
DOI: 10.1002/anie.201410236
|View full text |Cite
|
Sign up to set email alerts
|

High‐Resolution Single‐Molecule Fluorescence Imaging of Zeolite Aggregates within Real‐Life Fluid Catalytic Cracking Particles

Abstract: Fluid catalytic cracking (FCC) is a major process in oil refineries to produce gasoline and base chemicals from crude oil fractions. The spatial distribution and acidity of zeolite aggregates embedded within the 50–150 μm-sized FCC spheres heavily influence their catalytic performance. Single-molecule fluorescence-based imaging methods, namely nanometer accuracy by stochastic chemical reactions (NASCA) and super-resolution optical fluctuation imaging (SOFI) were used to study the catalytic activity of sub-micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
73
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 89 publications
(75 citation statements)
references
References 36 publications
2
73
0
Order By: Relevance
“…It was found that the average size of a zeolite aggregate domain for the fresh FCC catalyst particle (0.70 μm 2 , Figure a) is significantly larger than that of the ECAT1 (0.52 μm 2 , Figure b) and ECAT2 (0.55 μm 2 , Figure c) particles. The observed zeolite size distributions are consistent with other studies where conventional and single‐molecule confocal fluorescence microscopy were used to study FCC catalysts containing ZSM‐5 zeolites, thus supporting the use of La as a specific marker for pinpointing individual zeolite domains in a catalyst matrix …”
Section: Figuresupporting
confidence: 87%
“…It was found that the average size of a zeolite aggregate domain for the fresh FCC catalyst particle (0.70 μm 2 , Figure a) is significantly larger than that of the ECAT1 (0.52 μm 2 , Figure b) and ECAT2 (0.55 μm 2 , Figure c) particles. The observed zeolite size distributions are consistent with other studies where conventional and single‐molecule confocal fluorescence microscopy were used to study FCC catalysts containing ZSM‐5 zeolites, thus supporting the use of La as a specific marker for pinpointing individual zeolite domains in a catalyst matrix …”
Section: Figuresupporting
confidence: 87%
“…Alternatively, fluorescence microscopy, combined with fluorogenic probe molecules, enables the localization of single catalytic turnovers, and thus the location of accessible Brønsted acid sites, with up to 20 nanometer resolution. By accumulating these turnovers into catalytic activity maps, as done in nanometer accuracy by stochastic chemical reactions (NASCA) microscopy, the catalyst performance can be assessed at the nanoscale Hence, such measurements directly reveal the combined effect of acidity and accessibility, as these stochastic catalytic turnovers are localized while occurring on accessible acid sites.…”
Section: Figurementioning
confidence: 99%
“…The hyperspectral information gained from the TEFL maps revealed a spatial distribution of Brønsted acidity within the individual zeolite domains in different regions of the catalyst particle. We have also shown that sectioning of catalyst particles into thin layers is an effective strategy to investigate zeolite acidity in the central regions of the spherical particles, which are not easily accessible by super‐resolution fluorescence microscopy . These results demonstrate that TEFL can become a powerful and sensitive characterization tool to investigate single catalyst particles and reveal inter‐ and intra‐particle chemical variations with nanoscale spatial resolution.…”
Section: Figurementioning
confidence: 80%